The Impact of Error in Persona : Lilability of Police Investigators in Wrongful Arrest Cases - Adi Gunawan; Parningotan Malau; Wildani Khotami; Harly Clifford Jonas Salmon (PT. Anagata Sembagi Education, 2024)
Wrongful arrest in Indonesia is a serious problem in law enforcement that often results in physical suffering, psychological, and social losses for victims. One form of error that often occurs is “error in persona,” which is a misidentification that results in the arrest of an innocent person. This research uses normative juridical method with literature study and qualitative analysis to analyze the responsibility of investigators in cases of wrongful arrest. The purpose of this study is to understand the factors that cause errors in persona and their impact on victims and the legal system. The results show that misidentification often occurs due to inaccuracies in evidence collection, pressure to quickly resolve cases, and the use of inadequate investigative methods. In addition, the importance of fulfilling the legal procedures stipulated in the Criminal Procedure Code (KUHAP) is crucial to prevent these errors. Reforms in the investigation process, increased capacity of investigators, and the use of modern technology are necessary to minimize the risk of errors and ensure justice and the protection of human rights.